Plantar osteochondral fragments in young Standardbreds are associated with minimal joint inflammation at the time of surgical removal. (29th March 2022) - McCoy, Annette M.; Secor, Erica J.; Roady, Patrick J.; Gray, Sarah M.; Klein, Julie; Gutierrez‐Nibeyro, Santiago D.
Abstract: Background: Plantar osteochondral fragments (POF) are common but their effect on joint health of young Standardbreds in race training is largely unknown. Objectives: Evaluate the inflammatory effects of POF in metatarsophalangeal joints of young Standardbreds as a step towards developing evidence‐based recommendations for surgical removal. Study design: Cohort study. Methods: Forty‐nine Standardbred horses (age 11‐33 months) presented for surgical removal of POF from 56 metatarsophalangeal joints. Synovial tissue collected at arthroscopy was subjected to histopathology. IL‐1β, TNF‐α, and PGE‐2 were measured in synovial fluid using ELISA. Digital arthroscopy images were scored for inflammation. Racing performance data were retrieved from a public database. Results: Median time in race training prior to surgery was 8 weeks (IQR 4‐12; range 0‐40). There was minimal evidence of synovial inflammation as assessed by histopathology (median total score 2/20, IQR 0‐2, range 0‐5) or arthroscopy (median average total score 2.67/15, IQR 1.79‐4, range 0‐8.83). IL‐1β was not detected in any sample. TNF‐α (median 0 pg/mL, IQR 0‐0) and PGE‐2 (median 56.6 pg/mL, IRQ 40.5‐99.8) were measured at low levels. Weeks in training prior to surgery was associated with the number of starts in the season after surgery (incidence rate ratio 1.02, 95% CI 1.00, 1.04, P = .03). Main limitations: Small sample size from a single breed with a relatively short training time prior to surgery. Conclusions: There was minimal evidence of synovial inflammation in the metatarsophalangeal joints in this population of young Standardbred horses with POF. It is possible that POF may result in a different inflammatory response than other fragments because they are generally well‐embedded in situ. These findings suggest that, in Standardbreds, race training can commence several weeks prior to surgical removal of POF with minimal detrimental effects on joint health, although further investigation of long‐term effects of POF on joint health is warranted. Résumé: Introduction/Contexte: Les fragments plantaires ostéochondraux (POF) sont communs mais leur effet au niveau sur la santé articulaire chez les jeunes Standardbreds en entraînement de course demeure inconnu. Objectifs: Évaluer les effets inflammatoires des POF des articulations métatarsophalangiennes chez les jeunes Standardbreds dans le but d'ajouter à l'évidence disponible concernant les recommandations pour leur retrait chirurgical. Type d'étude: Étude de cohorte descriptive clinique. Méthodes: Quarante‐neuf chevaux Standardbreds (âgés 11‐33 mois) ont été présentés pour retrait chirurgical de POF en provenance de 56 articulations métatarsophalangiennes. Un échantillon de membrane synoviale recueilli au moment de l'arthroscopie a été soumis en histopathologie. IL‐1β, TNF‐α, and PGE‐2 ont été mesurés dans le liquide synovial par ELISA. Les images digitales d'arthroscopie ont été évaluées pour la présence d'inflammation. Les données de performance en course ont été retrouvées via une base de données publique. Résultats: Le temps médian de retour à l'entraînement suivant la procédure chirurgicale était de 8 semaines (IQR 4‐12; étendu 0‐40). Peu d'inflammation synoviale a été détectée en histopathologie (score médian total 2/20, IQR 0‐2, étendu 0‐5) ou arthroscopie (score médian total 2.67/15, IQR 1.79‐4, étendu 0‐8.83). IL‐1β a été détectée dans aucun échantillon. TNF‐α (médiane 0 pg/mL, IQR 0‐0) et PGE‐2 (médiane 56.6 pg/mL, IQR 40.5‐99.8) ont été détectés en faible quantité. Le nombre de semaines à l'entraînement avant la procédure chirurgicale était associé au nombre de départs pour la saison suivant la chirurgie (IRR 1.02, P = 0.03). Limites principales: Petite taille d'échantillon provenant d'une seule race de chevaux ayant une période d'entraînement relativement courte avant la procédure chirurgicale. Conclusions: Il y a peu d'évidence d'inflammation synoviale dans les articulations métatarsophalangiennes chez cette population de jeunes chevaux Standardbreds ayant des POF. Il est possible que les POF entraînent une réponse inflammatoire différente des autres fragments puisqu'ils sont généralement bien attachés dans l'articulation. Ces résultats suggèrent que chez les Standardbreds, l'entraînement de course puisse commencer plusieurs semaines avant le retrait chirurgical des POF en ayant des effets délétères minimaux pour la santé articulaire. Ceci dit, davantage de recherche est nécessaire pour établir les effets à long‐terme de ces POF sur la santé articulaire.